Práticas avaliativas de professores que ensinam matemática nos anos iniciais do ensino fundamental em Rondonópolis – MT - Oliveira, Kelly Bomfim Alves de (2016)
This research seeks to deepen the understanding of the importance of assessment practices of teachers who teach mathematics in Years Elementary School Initials. The research produced under this perspective of mathematics education have gone through a period of changes and influences throughout the school universe. The National Council of Teachers of Mathematics (NATIONAL COUNCIL OF TEACHERS OF MATHEMATICS, 1995), body that brings together the world teachers, directs that needs to reflect on the evaluation with the vision of school mathematics and propose from reforms of their education, which are developed new assessment strategies and practices. The objective of this research was to investigate the assessment practices developed by mathematics teachers of Early Years and their influence on mathematics learning in school. The research aims to answer the following question: The assessment practices of teachers interfere in the process of mathematical discipline of learning in Years You start of elementary school? Therefore, is guided in: Brazil (1997, 1998, 2002, 2013), Darsie (2010), Hoffmann (1999, 2000, 2005), Luckesi (2000), Sadovsky (2007), Saul (1999), Valente (2010) among others. Part of the premise that evaluation practice acts as a driving changes/reflections on teachers' conceptions and actions of mathematics in the process of teaching and learning and thus enables new ways of understanding of what and how to teach this discipline. This research used the approach and methodology of descriptive qualitative research and to analyze the statements and records of the teachers was used the interpretative method based on content analysis with objective to understand the ways of thinking and acting the same about the process of learning evaluation in Mathematics and assessment practices. The instruments used for analysis were: interviews, school records and observation. The data collected from the research show the following results: the evaluation practice happens daily in monitoring the development of the student, through, observations, interactions, discussions, corrections, guidance, interventions, diagnostic difficulties and advances, so you can plan and organize the classes. In the teaching and learning, evaluation is inextricably linked to the way teachers and students to pursue. For changes to occur in the evaluation process, requires research, reflection, depth analysis, new assessment strategies and practices that contribute to the construction of new knowledge, skills, actions of those involved.